Resonant Power Converters for Renewable Energy Applications: A Comprehensive Review - Bughneda, Ali; Salem, Mohamed; Alhuyi Nazari, Mohammad; Ishak, Dahaman; Kamarol, Mohamad; Alatai, Salah (Frontiers in Energy Research, 2022)
Studies on resonant power converters (RPCs) have received much attention due to the rapid growth of their potential in modern power and renewable energy applications such as photovoltaic, electric vehicles, wind, and fuel cells. Consequently, a significant number of studies focusing on RPC topologies for renewable energy applications is available. Generally, these studies have addressed several aspects, such as the development of their soft switching feature, smooth waveforms, high power density, and high efficiency. With this in mind, the present paper aims to review the development of the RPCs, challenges in their development, and comparison between common topologies as highlighted in literature. In addition, the use of RPCs in various applications of renewable energy is highlighted, focusing on some of the recently utilized topologies based on their constructions and achievements. There are still several issues and challenges in research that need to be considered for future improvement of the RPC performance in renewable energy applications. The improvement may require modifications on the circuit design or control strategies.